2017
DOI: 10.1111/jgs.14880
|View full text |Cite
|
Sign up to set email alerts
|

Restraint Use in Older Adults Receiving Home Care

Abstract: Use of restraints is common in older adults receiving home care nursing in Belgium. These results contribute to a better understanding of the complexity of use of restraints in home care, a situation that may be even more complex than in nursing homes and acute hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 28 publications
4
45
2
1
Order By: Relevance
“…The study by Scheepmans et al. () indicated that restraints were used in 24.7% of older adults receiving home care; however, in this study restraints included both physical restraints and non‐consensual care. Like the findings of Hamers et al.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The study by Scheepmans et al. () indicated that restraints were used in 24.7% of older adults receiving home care; however, in this study restraints included both physical restraints and non‐consensual care. Like the findings of Hamers et al.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, the order of restrictiveness of involuntary treatment use and feelings of discomfort when using involuntary treatment are more or less similar between the four groups: withholding aids and the telephone were considered the most restrictive types of non‐consensual care and fixation belts, wrist‐ and ankle belts are considered the most restrictive types of physical restraints by all caregivers. These types of involuntary treatment are the least requested and applied (Hamers et al., ; Scheepmans et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Scheepmans et al. ). To our knowledge, there is no relevant nursing guideline for physical restraint use has been published in mainland China; consequently, there is a lack of practice criteria for nurses and standard practices for physical restraint use among hospitals (Xu & Zheng ).…”
Section: Introductionmentioning
confidence: 97%
“…Physical restraint use seems to be common in various clinical settings. The rate of which is between 7% and 87% in acute care units, and is 24.7% in nursing homes (Azizpour et al 2017;Scheepmans et al 2017). To our knowledge, there is no relevant nursing guideline for physical restraint use has been published in mainland China; consequently, there is a lack of practice criteria for nurses and standard practices for physical restraint use among hospitals (Xu & Zheng 2010).…”
Section: Introductionmentioning
confidence: 99%